Freshwater crabs (Decapoda: Pseudothelphusidae) increase rates of leaf breakdown in a neotropical headwater stream. (21st May 2020) - Yang, Carol; Wenger, Seth J.; Rugenski, Amanda T.; Wehrtmann, Ingo S.; Connelly, Scott; Freeman, Mary C.
Abstract: Freshwater crabs are the largest macroconsumers in many neotropical headwater streams, but few studies have examined their roles in ecosystem processes such as leaf litter breakdown. As omnivorous macroconsumers, freshwater crabs affect multiple trophic levels. They may directly increase leaf breakdown through fragmentation and consumption or indirectly decrease breakdown by consuming other macroinvertebrates, including shredders and detritivores. In a headwater stream in Monteverde, Costa Rica, we conducted an in‐stream experiment with 40 enclosures to quantify the effects of pseudothelphusid crabs on both leaf breakdown and macroinvertebrate colonisation of leaves. Half of the enclosures were randomly selected to contain two crabs (mean carapace width = 30 mm) and half were controls without crabs. We sampled mixed leaf packs from the enclosures on days 11, 19, 28, 34, and 42. We found the leaves of one species ( Koanophyllon pittieri ) almost completely decomposed by day 28 in both treatments (crab versus no crab). The other two leaf species ( Meliosma idiopoda, Quercus brenesii ) composed the remaining leaf mass at the end of the experiment. At 42 days, enclosures with crabs had faster rates of leaf breakdown than those without crabs (with crabs: k = −0.020; without crabs: k = −0.016; p = 0.034). This suggests that the magnitude of direct leaf breakdown by crabs, due to fragmentation, consumption, or manipulation of leaves, was greater than any indirect effects on leaf breakdown via crab consumption of other leaf‐consuming species. Macroinvertebrate composition based on taxa abundances or biomasses did not significantly differ between treatments (ANOSIM; p = 0.73 and p = 0.65, respectively). Shredder and detritivore abundances and biomasses increased significantly through time (ANOVA; p ≤ 0.001), but there was no evidence of an effect of crab presence ( p > 0.2), nor were there significant interactions between crab presence and time ( p > 0.3). This is one of the first studies to quantify the effects of pseudothelphusid freshwater crabs on leaf breakdown rates. Our results suggest that these crabs can play a significant role in detrital processing in neotropical headwater streams. This study has also demonstrated that short‐term enclosure experiments are useful in measuring in‐stream effects of crab activity on leaf breakdown.